Faktor-Faktor Yang Mempengaruhi Fraud Dalam Kegiatan Pengadaan Barang dan Jasa - Nur Hidayati; J.M.V. Mulyadi (Magister Akuntansi Universitas Pancasila, 2017)
ABSTRACT The purpose of this study is to examine whether variables such as quality of goods/services procurement committee, income of goods/services procurement committee, procurement system and procurement system, procurement ethic of goods/services and internal control system have influence to fraud of goods/ services procurement in the ministry of health affairs agency. Population in this research is all auditor related in process of procurement of goods/services, while the object of research (sample) that is as much as 56 people. The technique of determining the sample using purposive sampling method. Data were tested using validity test, reliability test, multicolinearity test, heteroskedasticity test, multiple regression analysis, hypothesis test and coefficient of determination. The result of the research shows that the quality of procurement committee variables significantly and negatively affect the fraud of procurement of goods/services. The income of the procurement committee does not significantly affect the procurement of goods/services, procurement system and procedures have significant effect and negative to the goods/service procurement, ethics have significant effect and negative to the procurement of goods/services and internal control system significantly and negative to the fraud of procurement of goods/services. ABSTRAK Tujuan dari penelitian ini adalah untuk menguji apakah variabel seperti kualitas panitia pengadaan barang/jasa, penghasilan panitia pengadaan barang/jasa, sistem dan prosedur pengadaan barang/jasa, etika pengadaan barang/jasa, dan sistem pengendalian internal memiliki pengaruh terhadap fraud pengadaan barang/jasa di Lingkungan Instansi Kementerian Kesehatan RI. Populasi dalam penelitian ini adalah seluruh auditor yang terkait dalam proses pengadaan barang/jasa, sedangkan yang dijadikan objek penelitian (sampel) yaitu sebanyak 56 orang. Teknik penentuan sampel menggunakan metode purposive sampling. Data diuji menggunakan uji validitas, uji reliabilitas, uji multikolinearitas, uji heteroskedastisitas, analisis regresi berganda, uji hipotesis dan koefisien determinasi. Hasil penelitian menunjukkan bahwa variabel kualitas panitia pengadaan berpengaruh secara signifikan dan negatif terhadap fraud pengadaan barang/jasa. Penghasilan panitia pengadaan tidak berpengaruh secara signifikan terhadap terhadap fraud pengadaan barang/jasa, sistem dan prosedur pengadaan berpengaruh secara signifikan dan negatif terhadap fraud pengadaan barang/jasa, ketika berpengaruh secara signifikan dan negatif terhadap fraud pengadaan barang/jasa dan sistem pengendalian internal berpengaruh secara signifikan dan negatif terhadap fraud pengadaan barang/jasa. JEL Classification: M41, M42, H57